Neponset River Greenway: Tenean Beach to Morrissey Blvd and The Neponet Greenway Edgewater Trail - Stella A Lensing; SingNing Kuo; Kellan Lewis; Diana Walden (Fábos Conference on Landscape and Greenway Planning, 2025)
Neponset River Greenway Tenean Beach to Morrissey Blvd The Neponset River Greenway is an approximately 9-mile shared use pathway that connects suburban communities between the Blue Hills Reservation and Boston. Approximately 7 miles of the greenway has been completed from Neponset Valley Parkway to Senator Joseph Finnegan Park in Port Norfolk. The northern connection to Boston, Tenean Beach to Morrissey Boulevard, is currently under construction in partnership with MassDOT. The project is federally funded ($10,000,000) through the State Transportation Improvement Program and the Congestion Mitigation and Air Quality Program. The new approximately 0.9-mile section of the Neponset River Greenway will improve the habitat value of the corridor and provide a safe extension of the greenway to Morrissey Boulevard, with future connections to Castle Island. This section of trail consists mainly of an at-grade 10-ft wide paved surface, with a new, safe pedestrian crosswalk at Victory Rd, and a 670-ft elevated boardwalk structure over the tidal salt marsh in Dorchester Bay, and a large overlook deck with views of the Bay and Boston. Neponset Greenway Edgewater Trail The Metropolitan District Commission’s 1996 “A Master Plan for the Lower Neponset River Reservation” the described the importance of the river to the Massachusetts tribe: The name “Neponset” means “Harvest River,” which referred to the days during the year when Massachusetts tribe of the Algonquin Nation feasted off the schools of fish caught in the river, especially in the spring when the herring and smelts came in from the ocean to hurdle the rapids and spawn in the freshwater that flowed from the river’s source 27-miles upstream… Acquisition of the Neponset Marshes began in 1896, making these salt marshes the earliest in the state to be protected as natural assets. In the 1996 plan, the Edgewater Drive area of the present limit of work was envisioned as Edgewater Park, a 3-acre park along both sides of the river. DCR’s 2006 Neponset River Reservation Master Plan Phase II refers to the area as Section 4: Belnel Neighborhood to Mattapan Square. The current project will realize DCR’s vision for improved access to the river with entry points through the existing historic cobble wall, accessible trails, interpretive signs, and an overlook at the river’s edge. The trail construction will be an opportunity to remove invasive plants and restore the riverine habitat.